RESISTENSI DAN RESPON ETNIK AFRO-AMERIKA ATAS MARJINALISASI ETNIK ANGLO-AMERIKA DALAM PUISI-PUISI KARYA HUGHES - Sugi Iswalono (LITERA, 2014)
This study aims to describe the forms of and responses to racial hegemony and theAfro-American ethnic group’s self-identity in Hughes’s poems. It employed the qualitativedescriptive approach. The data sources were Hughes’s poems entitled “I, Too, SingAmerica”, “Let America be America Again”, and “Theme for English B”. The data wereanalyzed by means of the postcolonialism theory, enriched by historical, socio-cultural,and political information during the post-civil-war era till 1960s in the United States ofAmerica. The findings are as follows. First, racial hegemony appears in the form of thenegative stereotype of the Afro-American ethnic group. The negative stereotype leadsto the marginalization of the Afro-American ethnic group, reflected by the injusticeand tyranny by the majority ethnic group. Second, responses to racial hegemony aremanifested in the Afro-American ethnic group’s awareness of dignity, self-esteem, andself-confidence as foundations to demand equality and to show their existence amid thewhite people ethnic group’s domination. Third, the pride of ethnic identity is actually apotential to realize Amerian ideals as a nation highly respecting equality and diversityas aspired by the founding fathers.